Comprehensive Modeling of Gas Fluidized-Bed Reactors Allowing for Transients, Multiple Flow Regimes and Selective Removal of Species - Mahecha-Botero, Andres; Grace, John; Elnashaie, Said S.E.H.; Lim, C. Jim (International journal of chemical reactor engineering, 2006)
A multiphase reaction engineering model is being developed to investigate the dynamic and steady state behaviour of fluidized-bed catalytic reactors. It accounts for transients, axial and radial dispersion, temperature and pressure profiles, interphase mass and heat transfer, different hydrodynamic flow regimes, catalyst deactivation, reactions with changes in molar flows and various energy options. The model is general enough that it can treat catalytic systems, subject to mass and energy transfer resistances within the phases, as well as permeating membranes. It is able to handle multiple phases and regions (low-density phase, high-density phase, freeboard region and permselective membranes). The model reduces as special cases to a number of simpler fluidized bed reactor models previously reported in the literature, allowing evaluation of the influence of different simplifying assumptions. As a case study, the model is shown to simulate oxy-chlorination fluidized-bed reactors for the production of ethylene dichloride from ethylene, extending a recent paper by Abba et al. (Chem. Eng. Sci., (2002) 57, 4797-4807).